Norma e transgressão II - Carmen Soares (Documentos, 2011)
The publication of Norma & Transgressão II was motivated by the wealth and variety of the reflection around the various ways in which each community experiences its own identity in the regulatory activity and gesture of rule-breaking, as well as, at a later stage, the integration of the transgressions executed (experienced as a new field of expanded identity). This dynamic, which cuts across many disciplinary areas, leads to the question of the boundaries of the individual(local) I and of the (global) community: what does it mean to be strange and not to be? to what extent does the tense connection between the normative and the transgressive constitute a process that determines collective and individual behaviour through which human beings learn, advance, and understand themselves and others? With its multidisciplinary and transhistorical character, this book is destined not only for postgraduate students of Classical Studies, but also for the broader public beyond the academic sphere.